Phenomenology and the metaphysics of sight - Cimino, Antonio, 1979- (Studies in Contemporary Phenomenology, 2015)
The articles in Phenomenology and the Metaphysics of Sight explore the uses and resonances of the paradigm of sight across the phenomenological tradition, with particular reference to the works of Husserl, Heidegger, and Merleau-Ponty. The axes of this investigation are the phenomenological readings of the notion of sight in ancient Greek philosophy, the ways in which phenomenology leads us beyond the primacy of sight, and the rivalry between the paradigm of sight and those of touch and hearing. The aim of this collection is to demonstrate that the use of the paradigm of sight pervades phenomenology and partially explains both the development of its self-criticism and its view on the history of philosophy.